Age and socioeconomic disparities in cervical cancer incidence and mortality: a SEER-based analysis - Ou, Yuyi; Chokkakula, Santosh; Chong, Sio Mui; Wang, Hao; Si, Andrew In-Cheong; Jiang, Yong; Huang, Liying; Xu, Xiaohua; Yin, Chengliang; Lyu, Jun; Huang, Xiaobin; Shang, Hui-ling (Frontiers in Public Health, 2025)
BackgroundCervical cancer (CC) remains a significant global health challenge, with marked variations in incidence and mortality influenced by age, race, and economic status. This study examines age-related patterns in CC outcomes, focusing on racial disparities and socioeconomic factors using data from the SEER18 database.MethodsWe conducted a retrospective cohort study using data from the SEER 18 registries program from 2010 to 2015. Logistic regression models were used to assess factors associated with CC presence at diagnosis. Cox proportional hazard models and competing risk models examined all-cause mortality (ACM) and cancer-specific mortality (CSM). Restricted cubic spline (RCS) analysis was employed to investigate nonlinear relationships between age and CC outcomes.ResultsA total of 11,183 cases of invasive cervical cancer were identified. The study revealed significant disparities in CC outcomes based on race and socioeconomic status. Black women exhibited higher incidence and mortality rates compared to White women, with this disparity widening with age. The hazard model showed that Black race (adjusted sHR 1.199, 95% CI 1.086–1.323, p = 0.0003) and lower income (adjusted sHR 0.842 for income over $75,000, 95% CI 0.772–0.919, p < 0.0001) were associated with poorer outcomes. Marital status, histological type, cancer stage, and tumor grade were also significant predictors of CC outcomes. Advanced stage (regional: adjusted sHR 3.971, 95% CI 3.517–4.483; distant: adjusted sHR 10.635, 95% CI 9.207–12.285, both p < 0.0001) and higher tumor grade (poorly differentiated: adjusted sHR 1.667, 95% CI 1.432–1.941; undifferentiated: adjusted sHR 1.749, 95% CI 1.363–2.244, both p < 0.0001) were strongly associated with increased mortality risk.ConclusionThis analysis highlights substantial racial and socioeconomic disparities in cervical cancer outcomes, exacerbated with increasing age and advanced tumor characteristics. These findings emphasize the necessity for age and population specific screening and intervention strategies to improve survival and reduce inequities among high-risk groups.